Perfil Psicomotor En Niños De 11 Años De Grado Quinto En Instituciones Educativas Públicas De Zona Urbana Y Rural. Calarcá – Quindío (2019)
The study; The objective of this study was to identify the psychomotor profile in children of 11 years old in the fifth grade of primary school, of public educational institutions, of urban and rural areas, Calarcá - Quindío. Methods: Quantitative approach, non-experimental design of descriptive and correlational scope. Where 66 students participated (27 urban zone – 39 urban zone). The results showed that the population in general was found in an eupraxic profile; however, the girls presented higher values in the tonicity, balance and laterality factor; whereas, children, in the factors notion of the body, global praxia and fine praxia; highlighting that the spatio - temporal structuring factors and global praxia were marked in the lowest values and the factor, laterality in the highest. Conclusions: the students of the urban and rural area, presented similarities with respect to the BPM factors, categorizing the psychomotor profile into a normal assessment, with 86.4% of the students, highlighting that the rural area presented an assessment of good with 18.6% unlike the urban area that had 10%, however, no correlation was found between the gender variables and the sociodemographic zone.